Pengaruh Kompetensi Guru terhadap Hasil Belajar Siswa pada Mata Pelajaran IPS Terpadu di SMP Negeri 9 Limboto Kabupaten Gorontalo - Fadila Rizki Anisa Rahman; Melizubaida Mahmud; Maya Novrita Dama; Frahmawati Bumulo; Fatmawaty Damiti (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This study aims to determine whether there is an influence of teacher competence on students’ learning outcomes in Integrated Social Studies at SMP Negeri 9 Limboto, Gorontalo Regency. Teacher competence is a crucial factor in achieving successful learning, as competent teachers are able to manage the learning process effectively, attractively, and meaningfully for students. This research employed a quantitative approach with a total sample of 55 students selected proportionally. The instruments used were questionnaires designed to measure both teacher competence and students’ learning outcomes. Data were analyzed using a simple linear regression technique to examine the extent of the relationship between the two variables. The results of the analysis showed that teacher competence has a significant influence on students’ learning outcomes. The magnitude of the influence of teacher competence on learning outcomes was found to be 70.6%, while the remaining 29.4% was affected by other variables not examined in this study. These findings indicate that the higher the level of teacher competence, the better the students’ learning outcomes in Integrated Social Studies at SMP Negeri 9 Limboto. Therefore, improving teacher competence is essential in enhancing the quality of student learning outcomes.